Roystonea regia: Royal Palm - Timothy K. Broschat (EDIS, 2014)
The royal palm is a large majestic palm that is native to south Florida and Cuba. It is considered cold hardy to about 28°F or USDA Cold Hardiness Zone 10A. This species quickly grows to heights of 50–70 ft., with a spread of 20–25 ft., and has a smooth light gray trunk up to 2 ft. in diameter. It is ideal for landscaping streets, parks, and commercial properties, but becomes too large for typical residential landscapes. This revised 4-page fact sheet was written by T.K. Broschat and published by the UF Department of Environmental Horticulture, February 2014.